Estudio histológico comparativo de la reparación ósea entre hueso alveolar y extra-alveolar en los cerdos sometidos a osteotomía con alta y baja velocidad, con refrigeración líquida - Baldo de Toledo, Henrique José [UNESP]; Lima de Castro, Alvimar [UNESP]; Monti, Lira Marcela [UNESP]; Soubhia, Ana Maria Pires [UNESP] (My University, 2012)
Taking into account the bone repair process in pigs has shown a greater similarity among the histological variables studied compared to other biological models, the present study has as its aim to evaluate the histological bone repair process of osteotomy performed on alveolar and extra-alveolar bones, using drilling tools with liquid refrigeration. Material and method: Eighteen Large White pigs weighing between 20 and 25 Kg were divided into three groups of six animals in order to evaluate the osteotomy repairs with low and high speed in the alveolar bone and threes in the extra-alveolar area, study periods of 7, 14 and 28 days. Results: It was observed that in the alveolar bone at the postoperative times of 14 and 28 days, the best repair results were in the osteotomy performed with low speed, while in the 7 day postoperative period, the results with high speed were slightly better, in alveolar areas as well as extra-alveolar areas. There no statistically significant differences between the alveolar and extra-alveolar bone repair process. Conclusions: The repair process, by means of microscopic analysis in the alveolar and extra-alveolar areas, are similar with better results observed in osteotomies performed with low speed drills in the 14 and 28 day study periods, and at 7 days postoperative the results with high speed drills and refrigeration were slightly better. Research works using pigs as an animal model are perfectly viable. © 2011 SECOM.
Comparative study of bone repair between alveolar and extra-alveolar bone in pigs subjected to osteotomy at low speed and high speed with liquid refrigeration
Keywords: Bone regeneration; Mandibular; Osteotomy; Pigs